MANAGING SUSTAINABLE DEVELOPMENT OF RURAL TOURISM IN VOJVODINA - Njegovan, Zoran; Demirović, Dunja F; Radović, Gordana (International Journal of Economic Practice and Policy, 2015)
Rural tourism in Vojvodina has been recognized as a factor in the revitalization of the village in order to solve economic and demographic problems. However, rural tourism does not have clearly defined elements of the marketing mix (product, price, promotion and distribution), nor is its development on the basis of sustainable development. By using the SWOT analysis, in the paper is analyzed the current status of rural tourism in Vojvodina and suggestions are offered for overcoming existing problems and adequate use of potentials. Based on the analysis, it was concluded that farms, villages as tourism products, ethnic and eco-tourism as well as various events should be the basis of the product of rural tourism. Also, the work provides a possible management practices in rural tourism, in order to ensure its sustainable development.